(untitled) (Conferencea, 2022)
Fungi - the world of eukaryotic organisms (bulimi). Living at the expense of ready-made organic substances, goiter is a heterotrophic organism. It usually has life in plants, soil, water, animals or in their hands. Depending on the method of release, it becomes parasitic and Saprophytic. They are found in more than one hundred thousand species, harmful and useful for humans and animals. The science of fungi is called mycology.